Trabectedin Plus Pegylated Liposomal Doxorubicin in Recurrent Ovarian Cancer - Monk, Bradley J.; Herzog, Thomas J.; Kaye, Stanley B.; Krasner, Carolyn N.; Vermorken, Jan B.; Muggia, Franco M.; Pujade-Lauraine, Eric; Lisyanskaya, Alla S.; Makhson, Anatoly N.; Rolski, Janusz; Gorbounova, Vera A.; Ghatage, Prafull; et al. (Journal of clinical oncology, 2010)
The objective of this study was to compare the efficacy and safety of trabectedin plus pegylated liposomal doxorubicin (PLD) with that of PLD alone in women with recurrent ovarian cancer after failure of first-line, platinum-based chemotherapy. Women > or = 18 years, stratified by performance status (0 to 1 v 2) and platinum sensitivity, were randomly assigned to receive an intravenous infusion of PLD 30 mg/m(2) followed by a 3-hour infusion of trabectedin 1.1 mg/m(2) every 3 weeks or PLD 50 mg/m(2) every 4 weeks. The primary end point was progression-free survival (PFS) by independent radiology assessment. Patients (N = 672) were randomly assigned to trabectedin/PLD (n = 337) or PLD (n = 335). Median PFS was 7.3 months with trabectedin/PLD v 5.8 months with PLD (hazard ratio, 0.79; 95% CI, 0.65 to 0.96; P = .0190). For platinum-sensitive patients, median PFS was 9.2 months v 7.5 months, respectively (hazard ratio, 0.73; 95% CI, 0.56 to 0.95; P = .0170). Overall response rate (ORR) was 27.6% for trabectedin/PLD v 18.8% for PLD (P = .0080); for platinum-sensitive patients, it was 35.3% v 22.6% (P = .0042), respectively. ORR, PFS, and overall survival among platinum-resistant patients were not statistically different. Neutropenia was more common with trabectedin/PLD. Grade 3 to 4 transaminase elevations were also more common with the combination but were transient and noncumulative. Hand-foot syndrome and mucositis were less frequent with trabectedin/PLD than with PLD alone. When combined with PLD, trabectedin improves PFS and ORR over PLD alone with acceptable tolerance in the second-line treatment of recurrent ovarian cancer.